Shortcomings of the Clean Water Act - Bennett, Nick (Maine Policy Review, 2023)
Since the passage of the Clean Water Act in 1972, it has changed the nation’s rivers from open sewers to important commercial and recreational resources. There is no question that the CWA has changed our lives and the environment for the better, but it is a law with many limitations.